Impact of Post-operative Radiological Parameters on Total Knee Arthroplasty Functional Outcome - Turki, Karim; Abdennadher, Achraf; Mallat, Youssef; Ayari, Rabie; Triki, Ramy; Amri, Khalil (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Total knee arthroplasty (TKA) is effective in treating end-stage osteoarthritis. Nevertheless, 20% of patients remain unsatisfied with the outcome at 1 year. AIM: The aim of our study was to identify the radiological parameters influencing the functional result and patient’s quality of life (QOL). METHODS: We conducted a retrospective observational study of patients who underwent primary TKA between 2015 and 2019. Standard radiographs were used to assess alignment parameters, patellar height, and implant size. Knee function was assessed using the Knee Society Score (KSS) and the QOL through the “Sfax modified Western Ontario and McMaster Universities osteoarthritis index (WOMAC).” RESULTS: One hundred and twenty cases were analyzed. The results in terms of alignment showed on average: an overall alignment of 2.41° varus, a coronal orientation of the femoral component of 5.49° of valgus, a coronal orientation of the tibial component of 2.16° of varus, a flexion of the femoral component of 0.7°, and a tibial slope of 2.6° with posterior orientation. We identified 19 cases of Patella baja (PB) and seven cases of pseudo PB. We identified 18 cases of oversizing of the femoral implant and six cases of undersizing. The tibial implant was oversized in ten cases and undersized in three cases. Global alignment of the limb and coronal alignment of the tibial component significantly influenced KSS and WOMAC scores. There was also a significant association between patellar height, knee function, and QOL. Femoral component size and overhang of the tibial component showed a significant influence only on WOMAC score. CONCLUSION: Standard radiography can be effective and reliable to evaluate TKAs. According to our results, we may suggest a checklist aiming to optimize knee function and patient’s QOL. It should include mechanical alignment of the limb, coronal alignment of tibial component, prevention of iatrogenic patellar tendon shortening, and precision in implant size choice.